Novel occlusion tool software for pulmonary vein occlusion verification in atrial fibrillation cryoballoon ablation. (25th November 2020) - Solimene, F; Cauti, F.M; Stabile, G; Rossi, P; Schillaci, V; Polselli, M; Arestia, A; Iaia, L; Shopova, G; Bianchi, S
Abstract: Background: Optimal pulmonary vein (PV) occlusion, checked with selective contrast injection, is mandatory to obtain an effective PV isolation with a cryoballoon. Purpose: The purpose of this study was to verify the feasibility of a new dielectric sensing system in assessing PV occlusion during cryoballoon ablation in patients with atrial fibrillation (AF). Methods: We enrolled 25 consecutive patients with paroxysmal or persistent AF. After transseptal access a detailed image reconstruction of left atrium and PVs was achieved with a decapolar circular mapping catheter and a novel dielectric imaging system. The degree of PV occlusion with the inflated cryoballoon catheter was verified by a new occlusion tool software of the dielectric imaging system and compared to the angiography with dye injection in each PV. Results: A total of 114 PV cryoballoon occlusion were tested. The new occlusion tool software showed a 91.7% sensitivity and 81.5% specificity in assessing a complete PV occlusion verified with dye injection. The positive predictive value was 84.6% and the negative predictive value was 89.8%. Acute isolation was achieved in all PVs. No 30 days complications were observed. Conclusion: This is the first study that demonstrates the feasibility of a new occlusion tool software, using the novel dielectric imaging system, in verifying the degree of PV occlusion during cryoballoon ablation. Funding Acknowledgement: Type of funding source: None